MANAJEMEN RISIKO MUTU GULA KRISTAL PUTIH DI PABRIK GULA PADJARAKAN KABUPATEN PROBOLINGGO - Yuli Wibowo; Bambang Heri Purnomo; Erin Nur Putriani (AGROINTEK, 2018)
PG. Padjarakan is one of the state-owned sugar factory under PTPN XI. that exist in East Java. Currently, some companies engaged in the sugar industry are faced with the level of competition. This requires that the company is able to produce quality products and in accordance with market demand so that companies get the maximum profit.  A company in doing the development can not be separated from the risks that may or will occur. The purpose of this research are to identify risks, analyze risk level and formulate risk control strategy at Sugar factory of Padjarakan. The research method used to analyze the magnitude of risk factor using fuzzy logic and control strategy using analytical hierarchy process. The results show that the risk factors that affect PG. Padjarakan include raw material risk, processing risk and human resource risk, based on the calculation that the risk of Raw Materials is high. While the results of the calculation of the risk of the Processing Process are in the medium category. And the results of calculating the risk value of Human Resources are in the high category. And overall for aggregation values of these three risks using MatLab R2007b software, PG. Padjarakan is in the high risk category. For control strategies, the highest priority is Human Resource Training.